Perancangan Sistem Informasi Manajemen Tugas Akhir Berbasis Web Jurusan Teknik Sipil Fakultas Teknik Universitas Tanjungpura - Wulansari, Endah (Jurusan Informatika Universitas Tanjungpura, 2013)
Final Paper is a main subject that must befinished by the college students to end their studytime in college and get the Bachelor(B) degree. Inadministration process of final paper, there areseveral procedures that must be completed.Administration process of final paper in CivilEngineering Major, Engineering Faculty,Tanjungpura University nowadays still works in asimple computerized where the final paper data issaved in excel (*xls) and word (*doc) format intofolders that made by administration staffthemselves and still not reference to DBMS, untilneed to be developed to make the administrationservice work become easier in Civil EngineeringMajor, Engineering Faculty, TanjungpuraUniversity in the process of maintenance the finalpaper data, prepare the letters that needed inadministration process of final paper, and make thedata recapitulation from the administration processof that final paper. The purpose of this research isto produce the Sistem Informasi Manajemen TugasAkhir (SIMTA) in Civil Engineering Major,Engineering Faculty, Tanjungpura University thatcan fulfil all needs like assist the administrationstaff work to prepare the letters that needed as therequirement in administration process of finalpaper, help the college students and lecturer to dothe consultation for final paper, and display thesummary from final paper database in graph fromor table to the major executive staff. The system isstructured in web based by using PHPprogramming language and MySQL Database. Thetesting of this final paper information systemmanagement is using the user acceptance testmethod to know about the system work well or not.From the testing result that has been done show thisfinal paper information system management can bedone as final paper data processing service that canhelp the administration staff to prepare the lettersthat needed in final paper administration process ofCivil Engineering Major, Engineering Faculty,Tanjungpura University, online consultation mediabetween lecturer and college students, can beaccesed wherever and whenever by internetconnection, give the information summary fromfinal paper database, in graph form or table tomajor executive staff.